2019
DOI: 10.1108/jfbm-11-2017-0036
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between corporate governance and financial performance

Abstract: Purpose The purpose of this paper is to attempt to fill a research gap in the relationship between corporate governance mechanisms and financial performance of family and non-family firms’ by using a sample of non-financial firms listed on Amman Stock Exchange (ASE) for the period 2009–2015. Design/methodology/approach This research employs a quantitative method using data that include corporate governance mechanisms, firm characteristics and financial ratios of a sample of Jordanian listed firms in the ASE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
72
2
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 121 publications
(123 reference statements)
11
72
2
8
Order By: Relevance
“…Also, those institutions managed by a family structure have less agency costs and are more effective [2,29]. To elaborate on this fact, Saidat, Silva and Seaman, revealed that structured companies are less probably to obtain modified audit opinions than non-family structured companies [30]. In Jordan, the predominant type of ownership characteristics is the family business class [31].…”
Section: Introductionmentioning
confidence: 99%
“…Also, those institutions managed by a family structure have less agency costs and are more effective [2,29]. To elaborate on this fact, Saidat, Silva and Seaman, revealed that structured companies are less probably to obtain modified audit opinions than non-family structured companies [30]. In Jordan, the predominant type of ownership characteristics is the family business class [31].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of developed countries concerning corporate governance"s impact on financial performance do not apply to Jordan due to its significantly smaller firm size as compared to those in developed countries, and also as most firms are regulated as family businesses (Abbadi et al, 2016). The few studies that have been conducted in Jordan were either focused on the family financial firms (Saidat et al, 2019) or companies listed on a particular stock exchange (Mansur and Tangl, 2018). It lacks an examination of the impact of corporate governance, especially board composition on financial institutions" performance (Al Daoud et al, 2015;Abbadi et al, 2016;Al-Momani and Almomni, 2018).…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%
“…The study results showed that corporate governance quality, as well as diversity, has a positive effect on the corporate dividend policy. Saidat et al (2019) study on family and nonfamily firms in Jordan showed that corporate governance mechanisms substantially impact the family firms" performance.…”
Section: Mahtab and Abdullahmentioning
confidence: 99%
“…As a result, BOD could influence firm performance in many ways. Among them are corporate social responsibility (Sheela et al, 2016) and disclosure (Hussain, Rigoni & Orij, 2018;Omar & Amran, 2017), debt composition (Hussain, Ali, Thaker, & Ali, 2019) earning management (Abdullah, et al, 2018;, financial performance (Saidat, et al, 2019;Jubilee et al, 2018;Bhatt & Bhatt, 2017;Low et al, 2015), financial stability (Lassoued, 2018), investment (Badru et al, 2019), risk management (Poletti-Hughes & Briano-Turrent, 2019; Sanusi et al, 2017), stock market liquidity (Amer, Hussein, & Ali 2017), sustainability (Hussain et al, 2018), and tax aggressiveness (Kim & Zhang, 2016).…”
Section: Board Of Directors and Firm Performancementioning
confidence: 99%
“…Among them are advice task (Westphal, 1999), control task (Daily, Dalton & Cannella, 2003), networking task service task (Åberg, 2019), and (Hillman & Dalziel, 2003), strategic participation task (Pugliese, Bezemer, Zattoni, Huse, Van Den Bosch, & Vol, 2009). Moreover, past studies showed BOD influences firm performance in various manners (Saidat, Silva, & Seaman, 2019;Jubilee, Khong, & Hung, 2018;Bhatt & Bhatt, 2017;Low, Roberts, & Whiting, 2015).…”
Section: Introductionmentioning
confidence: 99%